2021
DOI: 10.1002/asia.202101244
|View full text |Cite
|
Sign up to set email alerts
|

A new photoactivable NO‐releasing {Ru−NO}6 ruthenium nitrosyl complex with a tetradentate ligand containing aniline and pyridine moieties

Abstract: A new type of photoactivable NO-releasing ruthenium nitrosyl complex, [Ru(EPBP)Cl(NO)], with a tetradentate ligand, N,N'-(ethane-1,2-diyldi-o-phenylene)-bis(pyridine-2carboxamide) (= H 2 EPBP) was synthesized. Single crystal Xray crystallography revealed that the complex has a distorted octahedral coordination geometry and NO is positioned at cis to Cl À ion. NO-photolysis was observed under a white room light. The photodissociation of RuÀ NO bond was identified by various techniques including X-ray crystallog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Previous experimental and theoretical investigations on the NO photodissociations of the {Ru–NO} 6 complexes have revealed that the electronic transitions initializing the dissociations changed from direct metal-to-ligand charge transfers (MLCT), dπ(Ru) → π*(Ru–NO), to indirect LLCT characters when {Ru–NO} 6 complexes contained the ligands of multidentate π-extended systems. 23,27,32,39,73–75 Our results show the effect of the size of the ligand π-systems and electron-donating abilities on the photoactive bands and give some insights into the future direction of the development of {Ru–NO} 6 complexes for PDT applications.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Previous experimental and theoretical investigations on the NO photodissociations of the {Ru–NO} 6 complexes have revealed that the electronic transitions initializing the dissociations changed from direct metal-to-ligand charge transfers (MLCT), dπ(Ru) → π*(Ru–NO), to indirect LLCT characters when {Ru–NO} 6 complexes contained the ligands of multidentate π-extended systems. 23,27,32,39,73–75 Our results show the effect of the size of the ligand π-systems and electron-donating abilities on the photoactive bands and give some insights into the future direction of the development of {Ru–NO} 6 complexes for PDT applications.…”
Section: Resultsmentioning
confidence: 78%
“…The observed 14 N nuclear hyperfine coupling constant ( A N ) of 12.65 G and the isotropic g -value ( g iso ) of 2.039 are in agreement with the previously reported g -values of the NO–Fe( ii )(MGD) 2 adducts. 32,38,66–69 UV/Vis, IR, X-ray crystallography, EPR, NMR, and spin-trap EPR investigations on 1 and 2 unambiguously demonstrate the photodissociation of the Ru( ii )(L)–NO + (L = salophen 2− or naphophen 2− ) bond to release the NO radical and solvent–bound Ru( iii )(L) (eqn (1)). …”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations